2017
DOI: 10.22270/jddt.v7i3.1449
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Oral Uptake of Amikacin Using Copolymers

Abstract: Amikacinis a semisynthetic derivative of Kanamycin; it was approved for clinical use in the U.S. in 1976. Amikacin is broadspectrum and potent aminoglycoside with limited clinical use owing high dose requirement.Many gram-negative bacteria, including many strains of Pseudomonas, Enterobacter, and serratiaare inhibited by 1-20 mcg/ml amikacin in vitro. After injection of 500mg of amikacin every 12hours (15mg/kg/d) intramuscularly, peak levels in serum are 10-30 mcg/ml. Amikacinis valuable because it was more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Therefore, to probe potential links with CRC metastasis, it is important to directly target gut microbes. In this study, we constructed mouse models for treatment with the non-absorbable antibiotics gentamicin and amikacin, which have minimal bioavailability from the intestine [33,34]. The subsequent systematic analysis of changes in immune and metabolite composition demonstrated that intestinal microbes promote tumor metastasis by modulating DCA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to probe potential links with CRC metastasis, it is important to directly target gut microbes. In this study, we constructed mouse models for treatment with the non-absorbable antibiotics gentamicin and amikacin, which have minimal bioavailability from the intestine [33,34]. The subsequent systematic analysis of changes in immune and metabolite composition demonstrated that intestinal microbes promote tumor metastasis by modulating DCA metabolism.…”
Section: Discussionmentioning
confidence: 99%